Income inequality and happiness: perceived or actual, widely or narrowly defined, fair or unfair, self- or community-centred inequality? - Knight, J; Gunatilaka, R (University of Oxford, 2020)
The effect of inequality on happiness should intrigue social scientists. Of the many dimensions of income inequality, we explore four, analysing a rich data set for China. Does actual or perceived inequality have a greater effect on happiness? We find that perceptions of inequality are the more important. How broad is the reference group with which people compare themselves? They report that it is narrow; and indeed narrowly defined inequality has the greater effect on happiness. Do perceptions of the degree of fairness of inequality matter? The degree of perceived fairness is found to ameliorate the adverse effect of inequality on happiness. Is it self-centred or community-centred inequality which affects happiness? Both measures of inequality have significant effects, but in opposite directions. The research and policy implications are discussed.